Determinig how membrane phospholipids regulate CNS myelination and myelin composition - Correia, Bárbara Catarina Gonçalves (2017)
Rhizomelic chondrodysplasia punctata (RCDP) is an autosomal recessive disorder characterized by a defect in peroxisomal enzymes responsible for the biosynthesis of plasmalogens. This leads to a deficiency of this type of glycerophospholipid, and patients present bone abnormalities, and mental retardation. This disorder can be caused by mutations in the GNPAT gene, which encodes the first enzyme necessary for plasmalogen synthesis. Some studies have shown that myelination in the peripheral and central nervous system is affected by the loss of plasmalogens. However, it is unknown how this defect in myelination is orchestrated in a cellular and molecular scenario. With this work, we showed that it is possible to use in vitro co-cultures of cortical neurons and oligodendrocytes, from WT and Gnpat KO mice, to investigate the relation between both cells and what leads to demyelination. This strategy can also help to test different candidates for therapies. Alkyl-glycerols have been indicated as an alternative precursor of plasmalogens, but until now their efficiency to restore plasmalogen levels is still not proven in nervous tissue. We used one type of alkyl-glycerol named 1-O-tetradecyl-glycerol, and it was able to restore the defective myelination in Gnpat KO co-cultures. Myelin is also rich in proteins, and some have important functions for compaction and maintenance of the myelin sheaths. Therefore, it is important to analyze how the proteins are affected by the lack of plasmalogens. We used Western blot to analyze different proteins present in compact and non-compact myelin. We observed a significant decrease in the amount of myelin basic proteins (MBP) in myelin isolated from brain and spinal cord of Gnpat KO mice. MBP is essential to keep the myelin sheaths compact and functional. Other proteins like tubulin polymerization-promoting protein (TPPP) showed no differences in brain or in spinal cord myelin, since this protein is known to regulate the differentiation of oligodendrocytes, and our previous results did not evidence any problems during differentiation.